The Importance of Existing Social Protection Programs for Mental Health in Pandemic Times - Teresa Molina; Yoon Y. Cho (Institute of Labor Economics (IZA), 2024)
When it comes to mental health, do social protection programs matter more in times of crisis? Using panel data from the Philippines around the onset of the COVID-19 pandemic, this study compares depression rates among beneficiaries of an existing conditional cash transfer program to those of non-beneficiaries of similar socioeconomic status. Depression rates were almost identical for the two groups in late 2019, but significantly lower for conditional cash transfer beneficiaries by July 2020, after the initiation of strict quarantine measures and a large emergency cash transfer program. One interpretation of the increased importance of the conditional cash transfer program during the pandemic is that these transfers have larger protective effects in times of vulnerability. Another possible reason is that the existing infrastructure of the program, by allowing for more timely distribution of the emergency cash, enhanced the effectiveness of the government's pandemic response for conditional cash transfer beneficiaries. This paper finds evidence supporting both explanations.
Keywords: I38; I31; H12; 330; crisis; cash transfers; social protection; mental health; COVID-19